A Multicenter Evaluation of the Seraph 100 Microbind Affinity Blood Filter for the Treatment of Severe COVID-19. (25th March 2022) - Chitty, Stephen A.; Mobbs, Sarah; Rifkin, Brian S.; Stogner, Steven W.; Lewis, Michael S.; Betancourt, Jaime; DellaVolpe, Jeffrey; Abouzahr, Fadi; Wilhelm, Andrew M.; Szerlip, Harold M.; Parikh, Amay; Gaeta, Robert M.; et al.
Abstract : OBJECTIVES: The Seraph100 Microbind Affinity Blood Filter (Seraph 100) (ExThera Medical, Martinez, CA) is an extracorporeal therapy that can remove pathogens from blood, including severe acute respiratory syndrome coronavirus 2. The aim of this study was to evaluate safety and efficacy of Seraph 100 treatment for COVID-19. DESIGN: Retrospective cohort study. SETTING: Nine participating ICUs. PATIENTS: COVID-19 patients treated with Seraph 100 ( n = 53) and control patients matched by study site ( n = 53). INTERVENTION: Treatment with Seraph 100. MEASUREMENTS AND MAIN RESULTS: At baseline, there were no differences between the groups in terms of sex, race/ethnicity, body mass index, and need for mechanical ventilation. However, patients in the Seraph 100 group were younger (median age, 54 yr; interquartile range [IQR], 41–65) compared with controls (median age, 64 yr; IQR, 56–69; p = 0.009). Charlson comorbidity index scores were lower in the Seraph 100 group (2; IQR, 0–3) compared with the control group (3; IQR, 2–4; p = 0.006). Acute Physiology and Chronic Health Evaluation II scores were also lower in Seraph 100 subjects (12; IQR, 9–17) compared with controls (16; IQR, 12–21; p = 0.011). The Seraph 100 group had higher vasopressor-free days with an incidence rate ratio of 1.30 on univariate analysis. This difference was not significant after adjustment. Seraph 100-treated subjects were less likely to die compared with controls (32.1% vs 64.2%; p = 0.001), a difference that remained significant after adjustment. However, no difference in mortality was observed in a post hoc analysis utilizing an external control group. In the full cohort of 86 treated patients, there were 177 total treatments, in which only three serious adverse events were recorded. CONCLUSIONS: Although this study did not demonstrate consistently significant clinical benefit across all endpoints and comparisons, the findings suggest that broad spectrum, pathogen agnostic, blood purification can be safely deployed to meet new pathogen threats while awaiting targeted therapies and vaccines.